Emission tax vs. permit trading under bounded rationality and dynamic markets. (January 2021) - Foramitti, Joël; Savin, Ivan; van den Bergh, Jeroen C.J.M.
Abstract: A price on emissions can be achieved through an emission tax or permit trading. The advantages and drawbacks of either instrument are debated. We present an agent-based model to compare their performance under bounded rationality and dynamic markets. It describes firms that face uncertainty about future demand and prices; use heuristic rules to decide production levels, trading prices, and technology adoption; and are heterogeneous in terms of production factors, abatement costs, and trading behavior. Using multiple evaluation criteria and a wide range of parameter values, we find that the main difference between the two policies lies in the fact that permit prices fall after successful abatement. This can lead to higher production levels under permit trading, but can also drive emission-efficient firms out of the market. Scarcity rents under permit trading can further create higher profit rates for firms, the extent of which is shown to depend on the mechanisms for market-clearing and initial allocation. Highlights: We compare an emission tax and permit trading in an uncertain and dynamic setting. We consider different mechanisms for permits' initial allocation and pricing. Low permit prices can create an advantage for certain emission-intensive producers. Scarcity rents of permits can create windfall profits, notably under grandfathering.